Assessment of IS‐innovation strategic alignment factors among universal banks in Ghana. Issue 4 (23rd January 2019) - Yaw Obeng, Asare; Mkhize, Peter L.
Abstract: There is a widespread acceptance of information system (IS) strategic alignment. How and whether IS strategic alignment creates value especially in developing countries remains a major challenge for most banks. Additionally, alignment scope is often general making it difficult to identify specific important strategic alignment factors. We explored factors perceived to influence IS‐innovation strategic alignment, their interrelationships, and consequential effects among six universal banks in Ghana. Primary data were obtained through interviews. The two‐dimensional solution accounted for 85.4% of the total variance with P value of 0.000 indicating strong dependency in the data. The findings indicate IS and innovation of the banks are well aligned, and innovative performance is an output of successful IS‐innovation alignment. Collaboration and IS strategic projects factors contributed strongly to the successful alignment. The findings provide bank managers with more reliable and actionable insights to determine the dimensions of alignment that contribute more or less to firm performance.